THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND ATTITUDES ABOUT TRIAGE WITH FAMILY ANXIETY LEVEL PATIENTS IN THE EMERGENCY ROOM OF THE KASEMBON HOSPITAL - Yunita, Astri; Suroso, Heri; Hasyim, ABD Wakhid; Tandilangi, Elmerilia; Tang, Li Yoong; Meilyana, Berna Detha; Maula, Liya Ni'matul (SYNTIFIC, 2024)
Background. Determination of triage in the process and handling can have an impact on the length of patient triage. Conditions that require the selection of this color accuracy require time according to their needs so this sometimes causes family anxiety about ignorance about the triage. The purpose of this study was to determine the relationship between the level of knowledge and attitudes about triage with the anxiety level of the patient's family in the emergency room of RSUI Madinah Kasembon. Research Method. The research design is a descriptive correlative cross-sectional approach with the Kendall tau test. The sampling technique used purposive sampling and got a total sample of 266 respondents the families of patients. The research variables were knowledge, attitude, and anxiety level. Findings. The results showed the characteristics of the family's knowledge level in the moderate category, the characteristics of the family's attitude in the unfavorable category, and the characteristics of the family's anxiety level in the moderate category. The results of data analysis showed that there was a relationship between the level of knowledge about triage with the anxiety level of the patient's family in the emergency room (signed p= 0.023) and there was a relationship between the attitude about triage with the anxiety level of the patient's family in the emergency room (signed p= 0.001). Conclusion. There is a relationship between the level of knowledge and attitudes about triage with the anxiety level of the patient's family in the emergency room of RSUI Madinah Kasembon.